Complicated inguino-scrotal bladder hernia: a case of two-step repair. Issue 2 (4th March 2017) - François, Jules; Defoort, Barbara; Muysoms, Filip
Abstract: Background: Inguino-scrotal sliding hernia of the bladder (IBH) is a rare condition. Frequently, it is asymptomatic but sometimes it can be complicated by urosepsis and incarceration. Case presentation: A 74-year-old male with an IBH was admitted to the intensive care unit with urosepsis, acute renal insufficiency and incarceration of the herniated bladder. A two-step approach was performed to repair this complicated hernia. Firstly, the incarcerated bladder was reduced during a laparoscopic, trans-abdominal approach. Ten days later – after treatment of the urosepsis with antibiotics and normalisation of the inflammatory parameters – a Lichtenstein hernia repair was completed. The laparoscopic approach allowed correcting the acute incarceration of the bladder with possibility to inspect the bladder for iatrogenic bladder perforation. And after treating the urosepsis with adequate antibiotics, the second step was performed through an open Lichtenstein hernia repair, thus minimising the risk of mesh infection. Conclusion: In case of an IBH, complicated by urosepsis, a laparoscopic reduction of the herniated bladder followed by a Lichtenstein hernia repair in a second time is a valid option.